EMPOWERING THE MARGINALISED COMMUNITIES IN MULTICULTURAL NIGERIA: THE ROLE OF COMMUNITY RADIO - Oluwalaanu Sanusi, Bernice; James Okunade, Sunday; Olatundun Jire-Oladiran, Grace (African Journal of Social and Behavioural Sciences, 2024)
In a country like Nigeria, characterized by people of different races, ethnicities, religion and nationalities, there are bound to be marginalised communities. These set of people are being treated insignificantly and rendered powerless in the society they live in. Community radio stations across the nation have taken it upon themselves to empower these marginalised communities and be the voice for the people, as it is vital in combating marginalisation because it gives marginalised people a forum to speak up, obtain pertinent information, and engage in public conversation. The aim of the study was to identify and examine the role of community radio in empowering the marginalised communities in a multicultural society like ours. This study adopted the development media theory, using qualitative methodology while secondary data was utilised. Other academics’ studies, as well as press articles served as sources. The study concludes that community radio is considered a very important aspect in rural areas and plays an active role in rural development. It helps cater for the information needs of the marginalised society in a multicultural society. In addition, community radio could be used as a tool to empower the marginalised or underprivileged and speak out against discrimination and social injustices in society. The study recommended that community radios should ensure access and participation, diversity, independence and locality. This is to make sure that members of the marginalised groups can express their problems and difficulties via the station.